Taxonomic notes on the antlion tribe Myrmeleontini Latreille (Neuroptera, Myrmeleontidae, Myrmeleontinae) from Pakistan, with description of a new species - Hassan, Muhammad Asghar; Zheng, Yuchen; Liu, Xingyue (European Journal of Taxonomy, 2022)
A new species of the myrmeleontine antlion genus Baliga Navás, 1912 (Neuroptera: Myrmeleontidae), Baliga kashmirensis sp. nov., from Azad Kashmir and Khyber Pakhtunkhwa Province of Pakistan is described and illustrated, representing the first record of Baliga from Pakistan. Three species of Myrmeleon Linnaeus, 1767 are re-described: M. hyalinus hyalinus Olivier, 1811, M. tenuipennis Rambur, 1842, and M. trivialis Gerstaecker, 1885. Myrmeleon bimaculatus Yang, 1999 syn. nov. originally described from China is considered to be a junior synonym of Myrmeleon tenuipennis Rambur, 1842. In addition, an annotated catalogue of all species of Myrmeleon known from Pakistan along with their distribution map, taxonomical notes and updated identification key to known genera and species are provided.